The role of jus cogens in resolving the intertemporal problem in Mau Mau torture claims and other historical injustices: a theoretical exploration - Mogere, Evelyn Kerubo (Department of Public Law, 2015)
The chief obstacle in the resolution of historical injustices in international law is the inter-temporal question, summarized as the requirement that positive substantive international law, as it stood at the time in which an injustice occurred, ought always to apply over latter laws. Jus cogens, being largely independent from positive international law, offers a possible resolution to this problem: a possibility that this thesis explores using Mau Mau torture claims as a case study. Present in much legal opinion on the question is a presumption that inter-temporal law applies unless state practice justifying an exception for jus cogens can be found. However, this necessarily subjects jus cogens to inter-temporality and contradicts the standard meaning of jus cogens and its superior status in the entire legal framework of international law. It is argued in this paper that the superiority of jus cogens in international law should be reflected in the application of the inter-temporal principle, as indeed it should in the application of all other inferior norms and principles wherever relevant subject matter is in issue. After the introduction in chapter one, the above-described problem in the scholarly approach to inter-temporal law and jus cogens is highlighted in chapters two and three, wherein an apparent normative conflict between jus cogens and inter-temporal law is demonstrated. But if jus cogens norms begin at an identifiable point in time and are prospective in nature, no over-lap and thus no contradiction can be spoken of where the matter occurred before the emergence of these norms, a problem tackled in chapter four. Difficulties in the standard definition of jus cogens found in article 53 of the Vienna Convention on the Law of Treaties are also discussed along with an argument for an unlimited temporal scope of application for 'humanitarian' peremptory norms. Lastly, chapter five approaches the problem through the prism of a balancing scale of competing interests. In short, this thesis argues that there is no threat to justice, law or truth in applying 'humanitarian' peremptory norms to old injustices in the area of state responsibility.